(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article investigates contemporary trends in preparing future teachers for class-leader roles by examining theoretical foundations and practical experiences. Recognizing the evolving “class leader” function as encompassing psychopedagogical, communicative, digital, and leadership competencies, the study reviews key approaches: individual-pedagogical adaptation, leadership competency development, competency-based models, and integration of digital and interactive methods. Employing a mixed-methods design, researchers conducted semi-structured interviews with 30 prospective teachers, surveyed 200 students via a five-point Likert questionnaire, and implemented a 12-week practical experiment contrasting traditional lecture-based instruction with interactive, digital, and reflective activities. Quantitative analysis using SPSS 26 and qualitative coding with NVivo 12 revealed that the experimental group achieved significantly higher average scores in leadership, communication, teamwork, and reflection (4.2 vs. 3.5; p < 0.05), as well as greater proficiency in digital tool usage (78% vs. 45%). The findings confirm the effectiveness of competency-based and digital methods in class-leader preparation and suggest directions for broader, longitudinal research to reinforce these innovative pedagogical practices.